2019
DOI: 10.1001/jamainternmed.2019.2478
|View full text |Cite|
|
Sign up to set email alerts
|

Association Between Soft Drink Consumption and Mortality in 10 European Countries

Abstract: IMPORTANCE Soft drinks are frequently consumed, but whether this consumption is associated with mortality risk is unknown and has been understudied in European populations to date. OBJECTIVE To examine the association between total, sugar-sweetened, and artificially sweetened soft drink consumption and subsequent total and cause-specific mortality. DESIGN, SETTING, AND PARTICIPANTS This population-based cohort study involved participants (n = 451 743 of the full cohort) in the European Prospective Investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
200
3
3

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(233 citation statements)
references
References 40 publications
13
200
3
3
Order By: Relevance
“…It has been recommended that high consumption of artificially sweetened beverages should be discouraged [3] and not be promoted as a safe substitute for sugarsweetened beverages [26]. Meta-analyses, of three and four studies, respectively, have demonstrated an association between consumption of artificially sweetened beverages and hypertension [27] and cardiovascular disease [4]. A meta-analysis of 17 studies showed that artificially sweetened beverages were also associated with type 2 diabetes, independent of adiposity [28].…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been recommended that high consumption of artificially sweetened beverages should be discouraged [3] and not be promoted as a safe substitute for sugarsweetened beverages [26]. Meta-analyses, of three and four studies, respectively, have demonstrated an association between consumption of artificially sweetened beverages and hypertension [27] and cardiovascular disease [4]. A meta-analysis of 17 studies showed that artificially sweetened beverages were also associated with type 2 diabetes, independent of adiposity [28].…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Individual studies have demonstrated associations with metabolic syndrome [15], stroke [29] and all-cause mortality [30]. However, in the EPIC, NHS and HPFS cohorts, and in the Women's Health Initiative Observational Study, only the highest intake of artificially sweetened beverages was associated with all-cause mortality [3][4][5], and a more recent systemic review and meta-analysis of randomised and non-randomised control trials and observational studies, of non-sugar sweeteners (including artificially sweetened beverages) was inconclusive in relation to whether they were associated with harm [31]. Our initial findings also suggested an association between artificially sweetened beverages and mortality in the highest intake category.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of stroke and renal failure are also higher in young adults with history of childhood obesity [89,90]. In a recent study published in JAMA, positive associations were observed between consumption of artificially sweetened soft drinks and death due to circulatory diseases (>2 drinks/day vs. <1 glass per month; HR 1.52; 95%CI 1.30-1.78, p = 0.001) [91].…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…The evaluation of behavioral and lifestyle interventions remains extremely rare in spite of their importance for developing effective population health strategies and establishing health systems. This notwithstanding, PH researchers and other non-HTA professionals frequently study a variety of approaches for prevention interventions that directly target the general population (22,23). However, associated recommendations and more generalized implementation of campaigns and interventions do not belong to their mainstream responsibilities.…”
Section: Discussionmentioning
confidence: 99%